On the Power of Simulation and Admissible Functions in Metric Fixed Point Theory - Areej S. S. Alharbi; Hamed H. Alsulami; Erdal Karapinar (Journal of Function Spaces)
We investigate the existence and uniqueness of certain operators which form a new contractive condition via the combining of the notions of admissible function and simulation function contained in the context of complete b-metric spaces. The given results not only unify but also generalize a number of existing results on the topic in the corresponding literature.